Preferensi Konsumen terhadap Produk Sayuran Organik (Studi Kasus Konsumen UD Fabela-Myfarm) di Bogor Jawa Barat - Chrysanthini, Bebby; Sumarwan, Ujang; Rifin, Amzul (Institut Pertanian Bogor, 2017)
This research aimed to analyze consumer preferences to organic-vegetables attributes in Fambela-Myfarm and recommend strategic implication to increase organic vegetables sales. This research use consumer preferences theory and theory of planned behaviour, design in this research are using decriptive-quantitative approach. Sampling method used are purposive sampling to 200 samples whom have purchased organic vegetables. Independet variable on this research consist of behavioral belief (x1), subjective norm (x2), perceived behavioral control (x3) to purchase intention (y). These variable are analyzed using multiple linear regression. The results of this research shows that behavioral belief variable does not significantly affecting purchase intention. Subjective norm and perceived behavioral control variables shows significant influence to purchase intention. This research implied that Fabela-Myfarm could formulized marketing strategy to increase sales by utilizing product, price, promotion, and distribution. This strategies aimed to attract consumer to increase quantity through quality, and balance to create a better profit overtime.